Imminent risk of predation reduces the relative strength of postcopulatory sexual selection in the guppy. (7th December 2020) - Glavaschi, Alexandra; Cattelan, Silvia; Grapputo, Alessandro; Pilastro, Andrea
Abstract : Fifty years of research on sperm competition has led to a very good understanding of the interspecific variation in sperm production traits. The reasons why this variation is often very large within populations have been less investigated. We suggest that the interaction between fluctuating environmental conditions and polyandry is a key phenomenon explaining such variation. We focus here on imminent predation risk (IPR). IPR impacts significantly several aspects of prey behaviour and reproduction, and it is expected to influence the operation of sexual selection before and after mating. We estimated the effect of IPR on the male opportunity for pre- and postcopulatory sexual selection in guppies ( Poecilia reticulata ), a livebearing fish where females prefer colourful males and mate multiply. We used a repeated-measures design, in which males were allowed to mate with different females either under IPR or in a predator-free condition. We found that IPR increased the total opportunity for sexual selection and reduced the relative contribution of postcopulatory sexual selection to male reproductive success. IPR is inherently variable and our results suggest that interspecific reproductive interference by predators may contribute towards maintaining the variation in sperm production within populations. This article is part of the theme issue 'Fifty years of sperm competition'.